Genome-wide mapping uncovers significant quantitative trait loci associated with yam mosaic virus infection, yield and dry matter content in White Guinea yam (Dioscorea rotundata Poir.) - Adjei, Emmanuel Amponsah; Odong, Thomas Lapaka; Esuma, Williams; Bhattacharjee, Ranjana; Agre, Paterne Angelot; Adebola, Patrick Olusanmi; Chamba, Emmanuel Boache; Asfaw, Asrat; Dramadri, Isaac Onziga; Mbabazi, Sharon Tusiime; Edema, Richard; Ozimati, Alfred Adebo; et al. (Frontiers in Horticulture, 2024)
Yam is an important crop for food security in East and West Africa due to its high market value and customer demand. High tuber quality with yield and disease resistance are the main traits for acceptability of yam cultivars across the tropical zone. There has been limited progress in enhancing the production and quality traits of yams, despite the significant socio-economic significance of this crop. To expedite the development of high-quality yam cultivars in Uganda, traits association study was conducted to identify genomic regions associated with key traits such as disease resistance, high yields, and dry matter content. The association mapping was conducted using with multi-random mixed linear model (mrMLM) used to compute the associations using five (5) genetic models. A total of 16 significant single nucleotide polymorphisms (SNPs) markers were identified to be associated with the traits studied. Gene identification analysis revealed the presence of key putative genes such as Vicilin-like seed storage protein At2g28490 (ARATH)and Growth-regulating factor 1 involved in a variety of functions ranging from storage and gene regulation for disease resistance. The results obtained from this work have significant implications for the in-depth analysis of the genetic structure underlying key traits in yam. Additionally, this study emphasizes the identification of SNP variants and genes that may be utilized for genomicinformed selection in order to enhance yield and disease resistance in yams.